Collector's edition innovative packaging and graphics - Tolley, Stuart; Jones, Ivan (London Thames & Hudson, 2014)
Collector's Edition is a celebration of the outstanding creative possibilities that print continues to offer in the age of the digital download. It is a global survey that brings together over 170 examples of innovative and inspired packaging from the worlds of music, book publishing and magazines that have been released as a collector's, limited or deluxe edition.

Organized into four sections -- boxed; multiples; hand; and extras -- each example is accompanied by a project description and vital reference information about the format, materials and finishes used in the design, and the client, record label, publisher and designer behind the work. A broad spectrum of formats and genres is included, ranging from editions of albums by international recording artists to ultra-rare and expensive publications.

Illustrated throughout with especially commissioned photography and including in-depth interviews with Stanley Donwood, Irma Boom, Alec Soth, Dinos Chapman, The Vinyl Factory, FUEL, Stefan Sagmeister and The Flaming Lips, collector's edition is an essential resource for all graphic designers and packaging designers.

With 481 colour illustrations.
Machine generated contents note: Boxed -- Box sets, boxed editions, large-format packaging and limited-edition collectibles -- Interview: Stanley Donwood Artist and writer -- Radiohead/Haruki Murakami -- Orchestral Manoeuvres in the Dark -- Mario Testino/Stroboscopic Artefacts -- Alan Moore & Mitch Jenkins/Bonobo -- mono.kultur/Silversun Pickups -- Shout Out Louds/Erased Tapes -- Eleh/Stephanie Solinas/Gustav Mahler -- Squarepusher/The Horrors/Fiona Tan -- Kishi Bashi/Slanted/Popol Vuh -- The Clarke & Ware Experiment -- Interview: Irma Boom Graphic designer -- Jennifer Butler & Irma Boom -- Arve Henriksen/Can/DJ Shadow -- Mumford & Sons/Julian Sartorius/Oasis -- Autechre/My Wet Calvin/Amon Tobin -- The Breeders/Air/The National -- Edgar Martins /:zoviet*france:/Warp -- Die Schachtel/Russian Criminal Tattoo -- WassinkLundgren/Muse -- Multiples -- Multiple covers, guest artists, collectible series and deluxe editions made from specialist materials --
Includes index.
Donated by Prof. Michelle Roxas
Keywords: Graphic arts; Packaging -- Design